Fabrication and installation of the Mu2e cryogenic distribution system. Issue 1 (1st May 2022) - White, M; Lamm, M; Hocker, A; Arnold, D; Tatkowski, G; Kilmer, J; Poloubotko, V; Tope, T; Huang, Y; Elementi, L; Badgley, K; Voirin, E; et al.
Abstract: The muon-to-electron conversion (Mu2e) experiment at Fermilab will be used to search for the charged lepton flavor-violating conversion of muons to electrons in the field of an atomic nucleus. The Mu2e experiment is currently in the construction stage. The scope of this paper is the cryogenic distribution system and superconducting power leads for four superconducting solenoid magnets: Production Solenoid (PS), an Upstream and Downstream Transport Solenoids (TSu and TSd) and Detector Solenoid (DS). The design of the cryogenic distribution system and the fabrication of several sub-systems was reported previously. This paper reports on additional fabrication and installation progress that has been performed over the past two years. Lessons learned during fabrication and testing of the cryogenic distribution system components are described. In particular, the challenges and solutions implemented for aluminum welding are reported. A description of the process used to qualify the welding procedure and welders for welding the aluminium stabilized NbTi superconducting power leads is provided. Additionally, the progress made with regards to installing the power leads into the cryogenic Feedboxes is covered.